Religion, privilèges et inégalités : vers un désétablissement de l’Église d’Angleterre ? - Hervé Picton (Revue LISA)
Since it was established in the 16th century, the Church of England has almost always enjoyed a number of privileges including a monopoly of civil and religious life. Inevitably, this has raised a number of problems in terms of inequalities and the discrimination, sometimes persecution, of religious minorities. Although the most blatant discriminations have been removed and relations between the various faiths pacified, it remains that in a modern, multi-faith democracy, establishment appears increasingly like an anomaly. Various but not always satisfactory options have been put forward in order to address this issue, including a more hospitable, inclusive establishment. Disestablishment in England is a slow process that has been at work for almost two centuries and it seems likely that the trend will continue until the Church of England is totally free from the State.